Analyzing the Influence of Financial Performance on CSR Expenditure: The Mediating Role of Sales Growth in Indonesia’s Mining Sector - Verbie; Ika Nur Azmi; Juanda Astarani (Institut Bisnis dan Informatika Kesatuan, 2025)
This study empirically examines the influence of financial performance measured by profitability and leverage on Corporate Social Responsibility (CSR) expenditure among mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. In addition to examining the direct relationships, the study also tests the mediating role of the sales growth rate (SGR) in bridging the effect of profitability and leverage on CSR expenditure. The data used are secondary data obtained from companies’ annual and sustainability reports, comprising a total of 54 observations over three years. The analysis employed multiple linear regression and the Sobel test to assess the effects of variables. The findings reveal that both profitability and leverage have a significant negative effect on CSR expenditure, while sales growth does not mediate these relationships. These results underscore that financial pressures during and after the COVID-19 pandemic have led companies to prioritize financial efficiency over CSR allocation, even when experiencing sales growth. By adopting agency theory as the conceptual framework, this study contributes to the advancement of sustainability accounting literature, both in academic discourse and corporate practice, particularly within the mining sector, which is highly vulnerable to global economic fluctuations and environmental regulatory pressures.